Efficacy and safety of natural Aloe Vera gel in the treatment of stable vitiligo - Somanaboina Padmakar; G. Ajay Kumar; Navneet Khurana; Sweta Kumari; Biplab Pal (Elsevier, 2023)
Background: Vitiligo is a condition that causes a patchy loss of skin pigmentation. The Aloe Vera plant has been used to treat a wide range of ailments, including skin diseases; however, little is known about its effectiveness in vitiligo. This study aimed to assess the efficacy and safety of natural Aloe Vera in stable vitiligo. Methods: A retrospective review of medical records was conducted on vitiligo patients who recommended natural Aloe Vera between July 2021 and August 2022. All patients were advised to apply natural Aloe Vera leaf pulp thrice daily for 6 months, along with sunlight exposure. Efficacy was measured as the proportion of patients achieving ≥75% re-pigmentation of the target lesion at the end of 24 weeks, which constituted a ''good response,'' while 50% or higher re-pigmentation constituted a ''better response.'' The extent of re-pigmentation was assessed as per the protocol and graded from 0 to 5. Safety was assessed as the proportion of patients reporting ≥1 adverse event at 24 weeks. Results: The results revealed that 19 (86.3%) patients responded positively after receiving 3 months of treatment: 4 patients repigmented 50-74%, 8 patients repigmented 25-49%, 7 patients repigmented 1-24%, and 3 patients didn't repigment at all. After completion of 6 months of therapy, 3 patients repigmented 75-99%, 4 patients repigmented 50-74%, 10 patients repigmented 25-49%, 2 patients repigmented 1-24%, and 3 patients didn't show any change in re-pigmentation. Only 2 (9%) patients showed 90% re-pigmentation (grade 6) at the end of the study. Stinging or burning sensations and pruritus were experienced by 3 patients within the first week of treatment. Conclusion: Natural Aloe Vera was found to be safe and fairly effective in the treatment of stable vitiligo. However, randomized controlled trials with larger sample size are recommended to verify the efficacy and safety of Aloe Vera in the treatment of vitiligo.